Pengaruh Interaksi Sosial Siswa terhadap Prestasi Belajar PAI - Rahmah, Jabar (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2016)
The students’ social interaction, in terms of the discussion activities among them, is directed to help the students understand the lesson of Islamic education given. The success of learning Islamic education is reflected in the students’ achievement. That is why, it is important to know the effect of the students’ social interaction to their achievement in learning Islamic education of IAIN Samarinda. This is a correlational study. The population of this research was the eighth and ninth grade students of MTs Antasari Samarinda which had 195 students and the sample of this study was 67 students. The researcher used the correlation Product Moment to analysis the study. The result of the study shows that the model of discussion as a social interaction in learning Fiqh and Aqidah Akhlak does not give any significant effect to the students’ achievement.